Impact of Additional Active Treatment for Prostate Cancer on Health-related Quality of Life of Men: Results from the EUPROMS 2.0 1-year Follow-up Survey - Lionne D.F. Venderbos; Sebastiaan Remmers; André Deschamps; John Dowling; Ernst-Günter Carl; Nuno Pereira-Azevedo; Monique J. Roobol (European Urology Open Science)
Background and objective: In 2019 and 2021, Europa Uomo initiated the Europa Uomo Patient Reported Outcome Study (EUPROMS) and the EUPROMS 2.0 survey, with the goal of collecting data on patients’ self-reported perspective on physical and mental well-being outside of a clinical trial setting, to be able to investigate the burden of prostate cancer (PCa) treatment from a patient-to-patient perspective. Acknowledging the importance of collecting quality of life (QoL) follow-up data, a 1-yr follow-up (1yrFU) study was conducted to assess the effect of additional PCa treatment on QoL. Methods: Men with PCa who participated in the EUPROMS 2.0 survey and indicated that they were open to collection of a follow-up measurement were reinvited to complete the 1yrFU survey. The EUPROMS 2.0 1yrFU survey included the validated European Quality of Life 5 Dimension 5 Level (EQ-5D-5L), European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire (EORTC-QLQ-C30), Expanded Prostate Cancer Index Composite Short Form (EPIC-26), and International Index of Erectile Function (IIEF)-15 overall satisfaction domains. Descriptive statistics were used to assess demographic characteristics and to analyze the patient-reported outcome data. Key findings and limitations: A total of 1006 (54%) men completed the survey. The median age at the time of questionnaire completion was 72 yr (interquartile range 66–76 yr). Of them, 641 men (64%) underwent no new treatment, while 365 men (36%) underwent new treatment, including 247 (247/365, 68%) for PCa. In total, 114 patients (46%) underwent new androgen deprivation therapy (ADT) and 81 (33%) new external beam radiotherapy (EBRT). It is indicated that the impact of new ADT and EBRT on sexual function is immediate and detrimental, and continues to last over time. However, for men who underwent EBRT or radical prostatectomy earlier and did not undergo new treatment, slight improvements on various domains are reported. Conclusions and clinical implications: The EUPROMS 2.0 1yrFU study provides additional information on treatments that are already in common use and will help future PCa patients to make informed and shared decisions on PCa treatment. Patient summary: The follow-up data on quality of life collected by Europa Uomo can be used to inform future prostate cancer (PCa) patients about the impact of undergoing (multiple) PCa treatment(s).